2022
DOI: 10.1161/strokeaha.121.037411
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stroke Subtype With Hemorrhagic Transformation Mediated by Thrombectomy Pass: Data From the ANGEL-ACT Registry

Abstract: Background: The role of stroke etiology subtype in patients with acute large vessel occlusion on the occurrence of hemorrhagic transformation (HT) after endovascular treatment is poorly studied, and which factors mediate their relationship remains largely unknown. We utilized nationwide registry data to explore the association of stroke subtype (cardioembolism versus large artery atherosclerosis) with HT and to identify the possible mediators. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…22 Therefore, enhancing healthcare infrastructure, including targeted public health promotion in remote regions and better emergency medical services during the transit are needed. Despite inconsistency regarding the association of atherosclerotic LVO with poor prognosis in prior studies, [23][24][25][26] we add to the current evidence with the findings that atherosclerosis-caused LVO was at 68% higher risk of functional dependency compared with cardioembolic LVO. Prior inconsistency in findings was likely due to variability in diagnostic accuracy (eg, accuracy of intracranial atherosclerosis diagnosis), peri-EVT or post-EVT antithrombotic use, and thrombectomy techniques.…”
Section: Discussionmentioning
confidence: 62%
“…22 Therefore, enhancing healthcare infrastructure, including targeted public health promotion in remote regions and better emergency medical services during the transit are needed. Despite inconsistency regarding the association of atherosclerotic LVO with poor prognosis in prior studies, [23][24][25][26] we add to the current evidence with the findings that atherosclerosis-caused LVO was at 68% higher risk of functional dependency compared with cardioembolic LVO. Prior inconsistency in findings was likely due to variability in diagnostic accuracy (eg, accuracy of intracranial atherosclerosis diagnosis), peri-EVT or post-EVT antithrombotic use, and thrombectomy techniques.…”
Section: Discussionmentioning
confidence: 62%
“…Accurate cause subtype diagnosis is crucial for guiding risk stratification, clinical management, and secondary prevention strategy. 42 , 43 The relationship between plasma hemostatic molecular markers and cause subtypes has been extensively studied, but with conflicting results. 13 , 14 , 15 , 16 , 17 In the present study, we found that cardioembolism stroke exhibited significantly higher levels of ischemic TAT and PIC compared with LAA stroke.…”
Section: Discussionmentioning
confidence: 99%